Tropicalism and Romanticism: Francisco Mourelle de la Rúa’s Journey around the Pacific Ocean (1780-1781) - José María GARCÍA SÁNCHEZ (Cuadernos Dieciochistas)
The torrid or tropical Zone limited by the two tropics of cancer and Capricorn was imagined by the greatest powers of the 18 century, Spain, France, and Great Britain as a meeting area of the otherness where the tropical discourses, ambivalent, appeared written either with dose of ferocity and infertility, or exoticism and abundance. Francisco Mourelle de la Rua was one of the most experienced sailors that plied the international waters during the last third of the eighteenth century, one of his trips included one of the «tropical» zones par excellence, the trip embarked from San Blas in Nayarit in Mexico and his return to Manila is the object of analysis of this study.